The Development of a Coaxial Electrospinning Formula Using Fish Gelatin/PBS as the Core for Structurally Intact Liposome Loading and Release - Wang, Haoyu; Xia, Runnan; Zhou, Mo; Williams, Gareth R; Amler, Evzen; Zhou, Feng-Lei; Tamaddon, Maryam; Liu, Chaozong (Polymers, 2025)
In electrospun scaffolds, coaxial electrospinning is gaining increased attention due to its potential for biocomponent encapsulation and controlled delivery. However, the encapsulation of biocomponents, such as liposomes, remains challenging because of their low stability in commonly used electrospinning solvents. This study, therefore, aims to develop a novel coaxial electrospinning formulation for crafting a liposome-encapsulated, rapid-release coaxial fiber. Liposomes demonstrated desirable stability in fish gelatin/phosphate-buffered saline (PBS) solutions, which remain liquid at room temperature and exhibit exceptional spinnability at concentrations exceeding 80 w/v% due to the reduction in surface tension. Fluorescent labelling examinations confirmed the successful encapsulation of liposomes within coaxial fibers electrospun from a 160 w/v% gelatin/PBS core and a 20 w/v% PCL/chloroform/N,N-dimethylformamide (DMF) shell. The gelatin/PBS core solution formed solid ends at the tips of the core-shell fiber post-spinning, while maintaining a liquid state within the shell, thereby enabling the encapsulation of liposomes within the PCL coaxial fiber. Upon exposure to medium, the solid ends dissolve, enabling the rapid release of liposomes. The successful development of this liposome-loaded electrospun coaxial fiber, using fish gelatin, highlights its potential for creating advanced liposome delivery systems.
Keywords: liposomes; PCL; coaxial electrospinning; fish gelatin